The conception of actor network in Jelekong Art and Culture Village of Bandung Regency (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Jelekong is an art and culture village in Baleendah Sub-district of Bandung Regency which is well known for its activities in paintings and wayang golek or puppet crafts. The village’s character related to art is also shaped by several actions and relationships between socio-technical actors apart from the existence of artists and their activities. This research was, therefore, conducted to describe Jelekong Village as a heterogeneous socio-technical network by identifying and analyzing several actors and actions using Actor-Network Theory (ANT) which is a qualitative research method. Five network-actor conception prepositions including 1) the will of actan, 2) actors, 3) composition and translation of action, 4) network locality, and 5) network representation were reviewed to determine the phenomenon of the heterogeneous network formed in the village. The results showed several factors required in becoming Jelekong Village network and they include 1) the artist's will to initiate art actions, 2) existence of sociotechnical agent such as actors and resources related to the artist, 3) a very complex art relationship, 4) establishment of an art environment such as a studio and gallery, and 5) the meaning of art space for artists as a forum to preserve arts and culture as well as potential economic resources.
Keywords: Action translation; Actors; Actor-network theory; Arts and culture; Heterogeneous networks; Jelekong Village